Diabetic Foot, Conservative Management. (Texas Journal of Medical Science, 2022)
Diabetic foot ulcers are serious complications of Diabetes Mellitus and are known to be resistant to conventional treatment; they may herald severe complications and may lead to lower limb amputation if not treated wisely. Objectives: To assess the efficacy of conservative management and LowLevel Laser Therapy (LLLT) in the treatment of diabetic foot ulcers. Setting: Baghdad Teaching Hospital. Time, from January 2015 through April 2020. Patients and methods: A prospective randamised study included (45) patients who were proved to have a diabetic foot ulcer, the ulcers were graded according to Wagner classification into six grades from (0 to 5), and patients with Wagner grades 1, 2, and 3 were treated conservativly by wound cleaning, controlling of blood sugar in the ward and send for laser therapy. Results: There were six patients with grade 1 ulcers, and all of them (100%) showed complete healing over a period of 3 weeks of conservative treatment and laser therapy. Also, 22 patients out of 25 (88%) with grade 2 ulcers and 11 patients out of 14 (78.6%) with grade 3 ulcers showed complete healing in about six weeks of treatment. Forty-five patients were treated by laser, and only six patients (13.3%) showed minor complications (itching, numbness, erythema, or even blisters), which were reported after the 2nd. Weak of treatment. Conclusion: Diabetic foot ulcers are a common problem in Baghdad Teaching Hospital; it is most commonly occure in patients with long-standing uncontrolled diabetes. Conservatie treatment by wound cleaning, controlling of blood sugar, and laser therapy (LLLT) was proved to be effective in treating grade 1,2 and 3 ulcers and decreasing the time of ulcer healing